2021
DOI: 10.1111/ele.13779
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance under constant temperatures can accurately predict insect development times across naturally variable microclimates

Abstract: External conditions can drive biological rates in ectotherms by directly influencing body temperatures. While estimating the temperature dependence of performance traits such as growth and development rate is feasible under controlled laboratory settings, predictions in nature are difficult. One major challenge lies in translating performance under constant conditions to fluctuating environments. Using the butterfly Pieris napi as model system, we show that development rate, an important fitness trait, can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 79 publications
(111 reference statements)
2
61
0
Order By: Relevance
“…The relevance of laboratory assays investigating development at constant temperatures for natural populations has repeatedly been questioned. However, several studies confirmed that such laboratory data can at least to some extent be extrapolated (e.g., Fischer et al, 2011 ; von Schmalensee et al, 2021 and literature therein). In any case, we have shown that temperature affects shell morphology.…”
Section: Discussionmentioning
confidence: 87%
“…The relevance of laboratory assays investigating development at constant temperatures for natural populations has repeatedly been questioned. However, several studies confirmed that such laboratory data can at least to some extent be extrapolated (e.g., Fischer et al, 2011 ; von Schmalensee et al, 2021 and literature therein). In any case, we have shown that temperature affects shell morphology.…”
Section: Discussionmentioning
confidence: 87%
“…This may lead to a difference in the duration of prewinter of as much as two months between individuals of the same population. Mean summer temperatures in microhabitats at the Swedish field site where our P. napi were collected range up to 20°C (von Schmalensee et al, 2021), and survival was reasonably high at this temperature, but more extreme thermal conditions will likely occur further south in the species range or under future climate change. Our prewinter and winter treatments were both constant, rather than reflecting natural seasonal and daily variation, which can intensify the metabolic costs of prewinter conditions (Williams, Marshall, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The potential responses of insects and other ectotherms to future climate change have largely been evaluated using predictions modeled from species‐specific thermal performance curves (Kingsolver et al, 2013 ; Sinclair et al, 2016 ; von Schmalensee et al, 2021 ) or studies that experimentally elevate temperature in a lab or field setting. Here, we instead used an innovative approach allowing us to make realistic inferences about organismal performance under climate warming scenarios.…”
Section: Discussionmentioning
confidence: 99%